Workflow Application Management Employee Attendance, Leave, And Overtime At SKK Migas Representative Office Surabaya - Jafar, Doddy Asmadi; Nurcahyawati, Vivine; Sutomo, Erwin (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
The attendance of employees at the company is one of the important factors considered by the company, from the attendance data can be seen employees attendance level such as how often an employee is late for work, how often the employee's consent, or even alpha. However, the process of managing existing attendance in the representative office of SKK Migas Surabaya has several problems, such as the absence of data delay and does not relate processes such as employee absence permit, leave, and service in the process of managing employee attendance. With this application can help offices SKK Migas Surabaya manage employee attendance, prevent data loss in the absence of the permitting process, and provide authorization in stages in the process of application for permission, leave, and overtime